Impacto das estratégias de coping na resiliência de atletas de vôlei de praia de alto rendimento - Belem, I. C.; Malheiros Caruzzo, N.; Andrade do Nascimento Junior, J. R.; Lopes Vieira, J. L.; Fiorese Vieira, L. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2014)
Studies have shown that for developing a resilient profile athletes must deal with adversities in sports using personal resources such as optimism, competitiveness, motivation, maturity, and persistence. The objective of this study was to analyze the impact of coping strategies on the resilience of beach volleyball athletes. Forty-eight adult athletes of the Banco do Brasil Beach Volleyball Circuit participated in the study. The following instruments were used: Athletic Coping Skills Inventory-28 (ACSI-28) and Connor-Davidson Resilience Scale (CD-RISC). The data were analyzed using the Shapiro-Wilk test, Mann-Whitney U test, repeated-measures ANOVA with post hoc Bonferroni test, Spearman`s correlation test, and simple linear regression (p<0.05). The coping skills that had an impact on the resilience of athletes were "personal coping resources" (48%), "coping with adversity" (33%), "confidence and motivation" (25%), "goal setting/mental preparation" (12%), and "coachability" (9%). Athletes invited to the Brazilian team showed high levels of resilience [median=91.50 (84.0-94.0)] and the most frequently used coping skills were "peaking under pressure" (MD=2.25), "coping with adversity" (MD=2.62), "goal setting/mental preparation" (MD=2.75) and "confidence and achievement motivation" (MD=2.75). It was concluded that the use of coping strategies to overcome problems, having defined goals, motivation and concentration during competitions have a significant impact on the development of a resilient profile in elite athletes.